ENFORCEMENT OF NARCOTICS ABUSE LAWS CLASS III CONTAINED IN MEDICINE COMIX IN TEENAGERS - Berliana Hajariah Maryanti; Muhtadi Muhtadi; HS Tisnanta (Universitas Labuhanbatu, 2023)
The widespread misuse of Komix cough medicine can be seen from the discovery of many packets of cough medicine in places where teenagers usually gather. Abuse of Komix cough medicine is increasingly widespread, as indicated by the frequent findings and increasing number of cases among teenagers in the Kanyurang village community. Efforts to overcome the abuse of class III narcotics contained in the drug Komix among teenagers in the Lampung Regional Police area are carried out with several efforts, including Pre-emptive, which is the first step for prevention carried out by the police by holding outreach and counseling. Preventive, is real prevention carried out by the Police in the form of vehicle raids in vulnerable areas where narcotics are distributed and trafficked. The final effort is Repressive, which has gone through several stages, namely inquiry, investigation, arrest, search, confiscation, examination, detention, and filing. The inhibiting factors in efforts to overcome the abuse of class III narcotics contained in the drug Komix among teenagers in the Lampung Regional Police are community factors and family factors, where there is a lack of understanding in the community, especially teenagers, about the dangers of drugs as well as social factors and the friendship environment. In efforts to overcome criminal acts through pre-emptive and preventive efforts, we can increase cooperation with religious institutions to strengthen faith for all levels of society and can tighten supervision, increase the intensity of patrols consistently, and carry out their duties and functions as law enforcement officers as regulated in the law. -invitation.keywords: Law Enforcement; Class III Narcotics; Komix Drugs.